The host-specific whale louse (Cyamus boopis) as a potential tool for interpreting humpback whale (Megaptera novaeangliae) migratory routes - Iwasa Arai, Tammy (2018)
The whale louse Cyamus boopis is a host-specific amphipod that parasitizes humpback whales (Megaptera novaeangliae) across the world. Humpback whales from the Southern Hemisphere are currently separated into seven breeding stocks, each with its own migration route to/from Antarctic waters. The aim of this study was to determine the population structure of C. boopis from the Southern Hemisphere using cytochrome oxydase I sequences, and compare it to that of its host species found in previous studies. High haplotype and nucleotide diversities in C. boopis were observed, and the populations from western south Atlantic (WSA: Brazil + Argentina − Breeding stock A) and western south Pacific (WSP: Australia - Breeding stock E) did not show any significant difference but were differentiated from populations of eastern south Atlantic (ESA: Namibia - Breeding stock B) and the north Pacific. The genetic homogeneity between WSA and WSP populations, might reveal a higher genetic transfer within the Southern Hemisphere, since the feeding grounds of whales which are distributed throughout the circumpolar Southern Ocean could allow inter-mixing of individuals from different breeding populations during the feeding season. The present data reinforces that population dynamics of humpback whales seem more complex than stable migration routes, which could have implications for both management of the species and cultural transmissions of behaviours.